Grid connected Control Strategy of New Direct drive AC Excited Wind Power Generation System - KANG Er liang; HUANG Shan wu; SU Xian he (Journal of Harbin University of Science and Technology)
A novel directdrive AC excited wind power generation system is introduced Based on the mathematical model of new directdrive AC excited generator, a noload gridconnected control strategy based on vector control is proposed The generatorside converter and gridside converter are double PWM converters, the generatorside converter uses stator voltage oriented vector control ,the gridside converter uses grid voltage oriented vector control, they are coordinated control to realize the DC bus voltage stability, active power and reactive power decoupling, adjustable power factor The excitation converter uses stator flux oriented vector control to control the noload voltage of the stator by controlling the excitation current to ensure the reliable operation of the generatorside PWM rectifierOn this basis, the control strategy is simulated and analyzed by using simulation software The simulation results show that the new system has good dynamic and static performance and can realize gridconnected operation when the wind speed changes in a large range The feasibility and effectiveness of the control strategy are verified